BIROKRASI PELAYANAN PUBLIK PEMBUATAN AKTE KELAHIRAN - Hasnizar, Raja (Jurnal Ilmu Administrasi Negara, 2016)
Bureaucracy Public Service Creation Birth Certificate. This study aims to determine the birth certificate of service in the district of Pasir Penyu Indragiri Hulu as well as factors that hinder. Data collected through interviews with informants consisting of a Section Head of Birth Certificate and Death of Population and Civil Registration Indragiri Hulu, administrative staff in five villages and people who never get the birth certificate services. Analysis of data is supported by the observation and documentation relating to the problems examined. The results showed that the child’s birth certificate service in the district of Pasir Penyu Indragiri Hulu seen from indicators of productivity, quality of service, responsiveness and responsibitas still not good